Merlin-Deficient Schwann Cells Are More Susceptible to Radiation Injury than Normal Schwann Cells In Vitro - Cohen, Erin; Pena, Stefanie; Mei, Christine; Bracho, Olena; Marples, Brian; Elsayyad, Nagy; Goncalves, Stefania; Ivan, Michael; Monje, Paula V.; Liu, Xue-Zhong; Fernandez-Valle, Cristina; Telischi, Fred; Dinh, Christine T. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objectives Vestibular schwannomas (VS) are intracranial tumors, which are caused by NF2 gene mutations that lead to loss of merlin protein. A treatment for VS is stereotactic radiosurgery, a form of radiation. To better understand the radiobiology of VS and radiation toxicity to adjacent structures, our main objectives were (1) investigate effects of single fraction (SF) radiation on viability, cytotoxicity, and apoptosis in normal Schwann cells (SCs) and merlin-deficient Schwann cells (MD-SCs) in vitro, and (2) analyze expression of double strand DNA breaks (γ-H2AX) and DNA repair protein Rad51 following irradiation.Study Design This is a basic science study.Setting This study is conducted in a research laboratory.Participants Patients did not participate in this study.Main Outcome Measures In irradiated normal SCs and MD-SCs (0–18 Gy), we measured (1) viability, cytotoxicity, and apoptosis using cell-based assays, and (2) percentage of cells with γ-H2AX and Rad51 on immunofluorescence.Results A high percentage of irradiated MD-SCs expressed γ-H2AX, which may explain the dose-dependent losses in viability in rodent and human cell lines. In comparison, the viabilities of normal SCs were only compromised at higher doses of radiation (>12 Gy, human SCs), which may be related to less Rad51 repair. There were no further reductions in viability in human MD-SCs beyond 9 Gy, suggesting that <9 Gy may be insufficient to initiate maximal tumor control.Conclusion The MD-SCs are more susceptible to radiation than normal SCs, in part through differential expression of γ-H2AX and Rad51. Understanding the radiobiology of MD-SCs and normal SCs is important for optimizing radiation protocols to maximize tumor control while limiting radiation toxicity in VS patients.
Keywords: radiobiology; Schwann cells; radiation; DNA damage; DNA repair; merlin-deficient; vestibular schwannoma